1980
DOI: 10.1542/peds.65.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Bilirubinometry: Preliminary Studies of Noninvasive Transcutaneous Bilirubin Meter in the Okayama National Hospital

Abstract: A new noninvasive bilirubinometer (Tc BM), which measures transcutaneous bilirubin level of the newborn, was developed as a joint effort by the present authors and the Minolta Camera Company, Ltd. A series of linear relationships were found to exist between total serum bilirubin concentration and yellowish skin color intensity in both term and low-birth-weight infants of Japanese ancestry. The instrument was examined for precision, accuracy, and technique-dependence. From these resulting relationships, it can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
3

Year Published

1981
1981
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(53 citation statements)
references
References 0 publications
1
49
0
3
Order By: Relevance
“…Established hyperbilirubinemia management strategies in term newborns are listed in Table 1. A transcutaneous bilirubin (TcB) measurement was developed by Yamanouchi et al in 1980 and used as a screen for hyperbilirubinemia. 1,2 Two major sets of treatment criteria based on total serum bilirubin (TSB) alone or TSB and serum unbound bilirubin (UB) were developed and became popular in Japan, [2][3][4] one of which, using TSB and UB reference values, was developed by Nakamura et al in 1992 (Table 2).…”
Section: Hyperbilirubinemia Management In Term Newbornsmentioning
confidence: 99%
See 1 more Smart Citation
“…Established hyperbilirubinemia management strategies in term newborns are listed in Table 1. A transcutaneous bilirubin (TcB) measurement was developed by Yamanouchi et al in 1980 and used as a screen for hyperbilirubinemia. 1,2 Two major sets of treatment criteria based on total serum bilirubin (TSB) alone or TSB and serum unbound bilirubin (UB) were developed and became popular in Japan, [2][3][4] one of which, using TSB and UB reference values, was developed by Nakamura et al in 1992 (Table 2).…”
Section: Hyperbilirubinemia Management In Term Newbornsmentioning
confidence: 99%
“…A transcutaneous bilirubin (TcB) measurement was developed by Yamanouchi et al in 1980 and used as a screen for hyperbilirubinemia. 1,2 Two major sets of treatment criteria based on total serum bilirubin (TSB) alone or TSB and serum unbound bilirubin (UB) were developed and became popular in Japan, [2][3][4] one of which, using TSB and UB reference values, was developed by Nakamura et al in 1992 (Table 2). 4,5 Treatment methods for hyperbilirubinemia using phototherapy (PT) and exchange blood transfusion (ET) were established.…”
Section: Hyperbilirubinemia Management In Term Newbornsmentioning
confidence: 99%
“…Other contributing factors may be a hemodynamic effect, that of hemoconcentration, and changes of skin color during crying as Lucey et a1 [5] have suggested. However, it is impossible for skin bilirubin to move directly from the skin tissues to the blood or elsewhere during crying; another study [7] has suggested that bilirubin in the skin cannot move easily, but takes several hours.…”
Section: Acta Paediatr Jpnmentioning
confidence: 99%
“…Many techniques, such as spectrophotometry and colorimetry, have been used in dermatology to study skin colour in health and disease (2)(3)(4)(5)(6)(7). They have been used to study response to UV radiation (evaluation of phototype and minimum erythemal dose), to assess drugs for treating inflammation and erythema, and to examine the correlation between transcutaneous bilirubin (TcB) measurements and serum concentrations of bilirubin (SB) in newborns with a view to reducing the need for blood samples (8)(9)(10)(11)(12)(13). Unlike adults, newborn infants have thin translucent skin, enabling clinical observation of certain conditions, such as hyperbilirubinaemia.…”
mentioning
confidence: 99%